Chemical and biochemical characterization of Ipomoea aquatica: genoprotective potential and inhibitory mechanism of its phytochemicals against α-amylase and α-glucosidase - Saikia, Kangkon; Dey, Saurav; Hazarika, Shabiha Nudrat; Handique, Gautam Kumar; Thakur, Debajit; Handique, Arun Kumar (Frontiers in Nutrition, 2023)
Ipomea aquatica, also known as water spinach, is an aquatic non-conventional leafy vegetable and is considered a healthy and seasonal delicacy in ethnic food culture. The study revealed the presence of rich chemical and biochemical composition in I. aquatica and antioxidant activities. Moreover, the plant extracts demonstrated significant DNA damage prevention activity against UV/H2O2-induced oxidative damage. High-resolution mass spectrometric analysis by UPLC-qTOF-MS/MS resulted in the identification of over 65 different compounds and 36 important secondary metabolites. Most of the compounds identified represented polyphenolic compounds, viz. polyphenol glycosides and phenolic acids, followed by alkaloids and terpenoids. A UPLC-DAD method was developed and quantified for 10 different polyphenolic compounds. Out of all the metabolites examined, a significant number of compounds were reported to have various bioactive properties, including antibacterial, antiviral, antitumor, hepatoprotection, and anti-depressant effects. The plant extracts were found to contain various compounds, including euphornin, lucidenic acid, and myricitin glycosides, which possess significant medicinal value. Metabolite analysis utilizing GC-MS revealed the presence of various fatty acids, amino acids, sugars, and organic acids. The analysis revealed the presence of essential unsaturated fatty acids such as α-linolenic acid as well as beneficial substances such as squalene., The evaluation of glycemic control activity was carried out by comprehending the inhibitory potential of α-amylase and α-glucosidase, outlining the kinetics of the inhibition process. The inhibitory activities were compared to those of acarbose and revealed stronger inhibition of α-glucosidase as compared to α-amylase. Furthermore, the mechanism of inhibition was determined using in silico analysis, which involved molecular docking and molecular dynamic simulation of the identified IA phytochemicals complexed with the hydrolase enzymes. The study generates convincing evidence that dietary intake of I. aquatica provides a positive influence on glycemic control along with various health-protective and health-promoting benefits.